Rapid and sensitive amplicon-based genome sequencing of SARS-CoV-2 - Park, Changwoo; Kim, Kwan Woo; Park, Dongju; Hassan, Zohaib ul; Park, Edmond Changkyun; Lee, Chang-Seop; Rahman, MD Tazikur; Yi, Hana; Kim, Seil (Frontiers in Microbiology, 2022)
As SARS-CoV-2 variants of concern emerged, the genome sequencing of SARS-CoV-2 strains became more important. In this study, SARS-CoV-2 was sequenced using amplicon-based genome sequencing with MinION. The primer panel used in this study consisted of only eleven primer panels and the size of the amplicons was approximately 3 kb. Full genome sequences were obtained with a hundred copies of the SARS-CoV-2 genome, and 92.33% and 75.39% of the genome sequences were obtained with ten copies of the SARS-CoV-2 genome. The few differences in nucleotide sequences originated from mutations in laboratory cultures and/or mixed nucleotide sequences. The quantification of the SARS-CoV-2 genomic RNA was done using RT-ddPCR methods, and the level of LoD indicated that this sequencing method can be used for any RT-qPCR positive clinical sample. The sequencing results of the SARS-CoV-2 variants and clinical samples showed that our methods were very reliable. The genome sequences of five individual clinical samples were almost identical, and the analysis of the sequence variance showed that most of these nucleotide substitutions were observed in the genome sequences of the other clinical samples, indicating this amplicon-based whole-genome sequencing method can be used in various clinical fields.